Is Stent Type Used in Snodgrass Method a Factor in Fistula Formation? - Sarac, M.; Bakal, U.; Tartar, T.; Canpolat, S.; Kazez, A. (Wolters Kluwer Medknow Publications, 2018)
Context: Snodgrass method (tubularized incised plate urethroplasty [TIPU]) is a widely used technique for hypospadias repair. Aim: It was aimed to compare the outcome of hypospadias repair with stenting using feeding tube compare with those with Foley catheter. Subjects and Methods: The demographic characteristics of the 123 patients who underwent hypospadias repair with Snodgrass method, the success of the applied method, and the factors affecting fistula complication were evaluated retrospectively. Patients were divided into two groups: those operated before January 2010 (Group A) and those who were operated after (Group B). In Group A patients, urethroplasty was performed using silicone Foley catheters, in which balloon of these catheters was filled by saline at appropriate size. In Group B, urethroplasty was performed using feeding catheter. Results: Group A and Group B consisted of 32 and 91 patients, respectively. Fistula developed in 10 (31.3%) and 4 (4.39%) patients in Group A and Group B, respectively. There was a statistically significant difference between the two groups in terms of the development of fistula complication (P = 0.0002). Conclusion: The use of a feeding catheter in TIPU could be a more advantageous than using a Foley catheter.
Keywords: Complication; fistula; hypospadias; stent; tubularized incised plate urethroplasty